Duolingo Application for Advancing English Speaking Skills - Nora Fitria; Muhammad Usman; Nora Sahara (Yayasan Keluarga Guru Mandiri, 2023)
The aspects of speaking are crucial to the effectiveness of speaking instruction, and the enhancement process can be done through applying technology in learning. This research aims to find out students’ perception of using Duolingo in improving English speaking skills and to explore which aspects can be enhanced by students in learning using the Duolingo application. This research employed a descriptive qualitative design. The samples in this study were students from a senior high school in Banda Aceh, totaling 20 students. To collect data, researchers used questionnaires and interviews as instruments. The result of the questionnaire in this research was analyzed by using percentages. The research results find that 90% of students claim that learning through the Duolingo application helps them improve their English speaking skills. Besides, the most improved aspect of speaking skills is vocabulary, followed by other aspects which increase significantly, such as pronunciation, grammar, and fluency. In this study, students responded positively; hence, the Duolingo application effectively improves students' speaking skills.